Hardware reconfigurable coding and evolution algorithm based on evolvable hardware - Ting WANG; Ju-long LAN; Jun-ting WU (Tongxin xuebao)
A planar mapping function increments chromosome coding method based on FPGA platform with SRAM-architecture was proposed.The method could improve hardware reconfiguration efficiency by coding mapping realized by double platform mapping of binary configurable file string.Meanwhile,a betterment difference evolution algorithm was proposed based on local optimal mechanism introduced.The algorithm could promote convergence rate and whole efficiency.Finally,the result of the algorithm emulation shows that:MDE improves disadvantage of difference evolution algorithm with local optimal and approaches actual optimization outcome.